The Bank Lending Channel of Monetary Transmission in Brazil A VECM Approach - de Mello, Luiz (OECD Economics Department Working Papers, 2009)
This paper tests for the existence of a bank lending channel in the transmission of monetary policy in Brazil using monthly aggregate data for the period 1995:12 through 2008:6. The test is carried out in a VECM setting that allows for multiple cointegrating relationships among the variables of interest. We find evidence of two cointegrating vectors, which we identify as bank loan demand and supply functions by testing for a number of exclusion and exogeneity restrictions on the cointegrating relationships. Loan supply is negatively related to the interbank deposit certificate rate in the long term, which confirms the existence of a lending channel for monetary transmission. The VECM's short-term dynamics show that loan demand is equilibrium-correcting. But short-term disequilibria in the supply of loans are corrected through changes in the interbank deposit certificate rate, suggesting that monetary policy plays a role in restoring equilibrium in the credit market by affecting the borrowing rate faced by banks to raise non-deposit funds. This Working Paper relates to the 2009 OECD Economic Survey of Brazil (www.oecd.org/eco/surveys/brazil)